CLUSTERING ANALYSIS ON FACTORS RESPONSIBLE FOR STUDENTS’ ACADEMIC LOW PERFORMANCE IN PLATEAU STATE POLYTECHNIC BARKING LADI, PLATEAU STATE - Jugul, Simon Dachung (FUDMA JOURNAL OF SCIENCES, 2025)
Low academic performance among students in tertiary institutions has become a significant concern, particularly in developing countries like Nigeria. This challenge has manifested in high failure rates, poor examination outcomes, and declining graduation statistics. Despite various efforts by institutions and governments to curb this trend, there remains a lack of comprehensive, data-driven analysis to pinpoint the underlying causes. This gap has limited the effectiveness of interventions, necessitating a more systematic approach. This study investigates the factors contributing to low academic performance among students at Plateau State Polytechnic Barkin Ladi, using a clustering analysis approach. The research identifies individual, institutional, and environmental factors influencing academic outcomes. Data were collected from 300 students through structured questionnaires and analyzed using hierarchical cluster analysis and principal component analysis. The findings reveal that motivation, study habits, quality of teaching, curriculum relevance, access to resources, parental involvement, peer influence, and socioeconomic status are critical factors. The study concludes that a holistic approach is necessary to address low academic performance, recommending targeted interventions to enhance student motivation, improve teaching quality, increase access to resources, strengthen parental and community involvement, and address socioeconomic barriers. This research provides insights for stakeholders in the educational sector to develop effective strategies for improving academic performance.